Exploration of Aspergillus fumigatus Ras pathways for novel antifungal drug targets - Abdallah, Qusai Al; Fortwendel, Jarrod R. (Frontiers in Microbiology, 2015)
Ras pathway signaling is a critical virulence determinant for pathogenic fungi. Localization of Ras to the plasma membrane (PM) is required for Ras network interactions supporting fungal growth and virulence. For example, loss of A. fumigatus RasA signaling at the PM via inhibition of palmitoylation leads to decreased growth, altered hyphal morphogenesis, decreased cell wall integrity and loss of virulence. In order to be properly localized and activated, Ras proteins must transit a series of post-translational modification (PTM) steps. These steps include farnesylation, proteolytic cleavage of terminal amino acids, carboxymethylation, and palmitoylation. Because Ras activation drives tumor development, Ras pathways have been extensively studied in mammalian cells as a potential target for anti-cancer therapy. Inhibitors of mammalian Ras interactions and PTM components have been, or are actively being, developed. This review will focus on the potential for building upon existing scaffolds to exploit fungal Ras proteins for therapy, synthesizing data from studies employing both mammalian and fungal systems.